ARTICULATION OF CURRICULAR CONTEXTS IN THE DESIGN OF HYBRID COURSES: CONTEXTUALIZED TEACHER EDUCATION - da Graça Moreira da Silva, Maria; Otilia José Montessanti Mathias, Maria; de Aquino Noffs, Neide (Revista Gênero e Interdisciplinaridade, 2025)
This article analyzes a teacher education experience developed in an undergraduate Pedagogy program, focusing on curricular articulation through the use of active methodologies in the design of hybrid courses. This qualitative research is grounded in critical action research and involved collaboration between faculty and students in the integration of thematic units aimed at developing proposals for pedagogical intervention. Data were produced through reflective journals, pedagogical documents, and systematic observations, and were analyzed in light of the articulation between theory and practice, the promotion of student agency, and context-based teacher education. The results highlight the potential of curricular articulation as a political-pedagogical dimension of educational processes, while also revealing structural limitations, such as the constrained role of interns and institutional rigidity. The study concludes that the integration of active methodologies, supervised internships, and interdisciplinarity contributes to a teacher education that is critical, collaborative, and committed to social transformation.